BIOECOLOGICAL CHARACTERISTICS OF EREBINAE MOTHS (LEPIDOPTERA) DISTRIBUTED IN DESERT BIOCENOSES (International Conference on Economics, Finance, Banking and Management, 2025)
This article presents an overview of the distribution, biology, and ecological characteristics of moths belonging to the subfamily Erebinae, which are found in desert biocenoses. It includes a literature review on the topic, as well as a list of 28 species belonging to five tribes (Anydrophilini, Euclidiini, Pandesmini, Melipotini, and Pericymini), along with data on their collection time and location, phenological aspects, and developmental stages.